Development of Animated Emergency Drills Video to Enhance Early Childhood Understanding of Fire Disasters - Sitepu, Juli Maini; Masitah, Widya; Nasution, Mawaddah; Ginting, Nurman (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This research aims to develop an animated video to enhance early childhood understanding of fire safety procedures. The study employs a modified Research and Development (R&D) model based on Borg and Gall’s framework, comprising six stages: identifying potential and problems, collecting initial data, designing media, validating media, revising the design, and conducting product trials. The video, created using Adobe After Effects and Adobe Animate, was tested on 38 children at RA Tarbiyah Islamiyah. Data collection involved three types of questionnaires: media validation, content validation, and children's comprehension assessment. Validators and teachers evaluated each questionnaire using a checklist scale. Data analysis employed qualitative and quantitative methods to assess the effectiveness of educational media. Results demonstrated a significant improvement in children's understanding of fire emergencies, with pre-test scores averaging 62% and post-test scores at 74.8%. The animated video effectively visualised fire scenarios in a realistic yet comprehensible manner for children, reinforcing safety messages and encouraging prompt and safe responses during fires. The study concludes that animated videos are compelling educational tools for enhancing disaster preparedness among young children. The implications of this research suggest that early childhood education programs should integrate disaster preparedness training into their curricula. Future research should explore the long-term impacts of such interventions, assess their applicability in diverse educational settings, and incorporate additional multimedia elements to enhance engagement and educational outcomes. Collaboration between educators, disaster management professionals, and digital media experts is essential for developing comprehensive and practical safety education resources.